The Roles of Environmental Concern Effectiveness on Customer Satisfaction towards Organic Products - R. Sangeetha, Dr. A. Geetha (Drugs and Cell Therapies in Hematology, 2021)
In recent times, the concepts like the environmental protection, green revolution, sustainable development, protection of our planet earth, going green have turned out to be as a natural occurrence in day-to-day life of human beings. The technique of green marketing has been used by several firms for implementing the aforesaid concepts as well as for satisfying the requirements of the customers who care for the environment and really are concerned about it. In this view, the present study has been done to explore the influence of environmental concern over the customer satisfaction regarding the organic food products. The respondents of the study are the consumers of organic food products in Chennai and the number of respondents selected for the study is 100. The technique of selecting the respondents is Simple random sampling and the instrument used for data collection is a questionnaire. The tool used for analysing the collected data is Regression analysis. The findings of the analysis exhibit the fact that environmental concern is seen to predict customer satisfaction of organic product purchasers.